Re-Thinking Therapeutic Cultures: Tracing Change and Continuity in a Time of Crisis and Change - Nehring, Daniel (2024)
This introduction to the special section on therapeutic networks explores two questions: To what extent and in which ways does the hypothesis of the western therapeutization and psychologization assumption still hold in the world of the 2020s? What therapeutic discourses and institutionally situated forms of therapeutic experience and practice are salient today?The papers commented and described in this introduction to the dossier set out some initial answers to these questions and highlight some meaningful avenues for future research. We seek to construct a rationale for this re-examination of contemporary therapeutic cultures and the meanings and uses of the therapeutic in everyday life. Our attendant argument proceeds in three steps. First, we map the interdisciplinary field of research on therapeutic cultures, highlighting key axes of enquiry and their empirical and conceptual fundaments. Second, we introduce the papers of this special section and discuss how they speak to these questions and concerns. Finally, our conclusion summarises the case for the broader relevance of research on therapeutic cultures to sociology at large.